2012
DOI: 10.5152/akd.2012.213
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan ameliorates the expression of fibrotic related growth factors and collagen-1 in diabetic mice

Abstract: Objective: To investigate the potential beneficial effect of bosentan in ameliorating fibrotic agents in diabetic mice. Methods: Male 6-week old C57BL/6 mice were divided into 3 groups (N=20): Control group, diabetes mellitus (DM) group and DM-B group (diabetes with bosentan group). Streptozotocin (STZ) was injected as 200 mg/Kg for single dose, i.p. (intraperitoneal injection). Fasting blood glucose (FBG) was measured at 0-, 1-, 2-week after STZ injection to confirm that diabetes was induced in the mice. Bose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In general, ETA‐selective antagonists have consistently proven to improve renal function in various animal models of CKD. Some animal data have also shown that a non‐selective antagonist, such as bosentan, can produce beneficial effects in a diabetic kidney disease model . Saleh and colleagues directly compared a combined vs. ETA selective antagonist in the type 1 diabetic rat model and observed that while the ETA selective antagonist produced a more rapid decline in proteinuria, after 1 week treatment the decline in proteinuria was similar between the two types of antagonists .…”
Section: Role Of Endothelin In Chronic Kidney Disease: Experimental Mmentioning
confidence: 99%
“…In general, ETA‐selective antagonists have consistently proven to improve renal function in various animal models of CKD. Some animal data have also shown that a non‐selective antagonist, such as bosentan, can produce beneficial effects in a diabetic kidney disease model . Saleh and colleagues directly compared a combined vs. ETA selective antagonist in the type 1 diabetic rat model and observed that while the ETA selective antagonist produced a more rapid decline in proteinuria, after 1 week treatment the decline in proteinuria was similar between the two types of antagonists .…”
Section: Role Of Endothelin In Chronic Kidney Disease: Experimental Mmentioning
confidence: 99%
“…For example, mice required higher doses of STZ for inducing DM compared with other animals. While in ICR mice DM can be induced with comparatively lower doses (90–150 mg/kg), C57BL/6 mice need approximately 200 mg/kg dose of STZ [40, 4248]. Immunodeficient mice tend to need less dose of STZ than other wild-type strains.…”
Section: Animal Models Of Dm For Islet Researchmentioning
confidence: 99%
“…After two weeks inductions, the GLU-AC was about 170 mg/dl which is more the previous DM GLU-AC criteria in ICR strain (20). The diabetes physiological features, such like GLU-AC became more severe (higher) over the time prolonged after STZ induction (36) and the GLU-AC also sub-stantially increase from 171 ± 12 mg/dl (the 3rd week after induction) to 373 ± 36 mg/dl (the 6th week after induction) (Fig. 4, A and B) which is consistent to previous report.…”
Section: Discussionmentioning
confidence: 62%